River Jhelum, Kashmir Valley : (The international consultany group of the national board of fisheries, 1999)
This book introduces the conceps of aquatic environmantal impact assessment (AEIA), by evaluating standardised sampling methods for water chemistry, benthic invertebrates and the fish fauna. The book also contains detailed systematic analyses of the benthic invertebrates and the fihes, thus making it a valuable reference book for similar studies in the region and world wide.